1996
DOI: 10.1183/09031936.96.09030565
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein-A levels increase during Pneumocystis carinii pneumonia in the rat

Abstract: S Su ur rf fa ac ct ta an nt t p pr ro ot te ei in n--A A l le ev ve el ls s i in nc cr re ea as se e d du ur ri in ng g P Pn ne eu um mo oc cy ys st ti is s c ca ar ri in ni ii i p pn ne eu um mo on ni ia a i in n t th he e r ra at t There was a severalfold increase in SP-A protein and mRNA levels in uninfected glucocorticoid-treated rats. However, contrary to what has been reported with the surfactant-associated lipids, SP-A mRNA and protein levels in P. carinii-infected animals were significantly higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…We observed a marked increase in SP-A and SP-D (up to three-fold) in PCP patients, which was paralleled by virtually unchanged SP-B and SP-C concentrations in both the large surfactant aggregate fraction and cell-depleted but further unprocessed BALF (data not given in detail). In the context of SP-A and SP-D, these findings are in accordance with previous clinical (33,34) and animal (31,32,35) studies of PCP. They conflict, however, with other reports concerning SP-B and SP-C, where previous studies in animal models of PCP suggested a significant suppression of SP-B and SP-C Our study is limited in that only HIVpositive patients with signs of parenchymal lung disease were subjected to bronchoscopy and BAL; thus, HIV-positive patients without any sign of parenchymal lung disease were not included.…”
Section: Discussionsupporting
confidence: 92%
“…We observed a marked increase in SP-A and SP-D (up to three-fold) in PCP patients, which was paralleled by virtually unchanged SP-B and SP-C concentrations in both the large surfactant aggregate fraction and cell-depleted but further unprocessed BALF (data not given in detail). In the context of SP-A and SP-D, these findings are in accordance with previous clinical (33,34) and animal (31,32,35) studies of PCP. They conflict, however, with other reports concerning SP-B and SP-C, where previous studies in animal models of PCP suggested a significant suppression of SP-B and SP-C Our study is limited in that only HIVpositive patients with signs of parenchymal lung disease were subjected to bronchoscopy and BAL; thus, HIV-positive patients without any sign of parenchymal lung disease were not included.…”
Section: Discussionsupporting
confidence: 92%
“…Low levels of SP-A have also been found in other inflammatory disorders of the lung, including pulmonary fibrosis and cystic fibrosis (17,31). Conversely, patients with AIDS-related pneumonia and specifically Pneumocystis carinii pneumonia have elevated levels of SP-A (22,23). We concluded that the reductions in SP-A levels in TB patients are regional in nature and occur only in the radiographically involved lung segments.…”
Section: Discussionmentioning
confidence: 79%
“…Immunohistochemistry of lung sections from Pneumocystis-infected mice demonstrates that upregulation of SP-A was localized to regions of atelectasis and cellular infiltrates containing organisms (3). In a corticosteroid-treated rat model of PCP the SP-A levels are also reported to be increased (50,58) and, similarly, BAL samples from HIV-infected patients with PCP have an elevated SP-A content (49). SP-A has been shown to bind to isolated Pneumocystis organisms in a calcium-and mannosedependent manner via its carbohydrate recognition domain to gpA (gp-120), the major glycoprotein found on cell surfaces of trophozoites and cysts (69).…”
mentioning
confidence: 99%